FRI0004 Inhibition of Phosphodiesterase 4 (PDE4) Reduces Dermal Fibrosis by Interfering with The Release of Pro-Fibrotic Cytokines from M2-Macrophages. (15th July 2016) - Maier, C.; Ramming, A.; Schett, G.; Distler, J.H.; Beyer, C.
Abstract : Background: PDE4 catalyses the breakdown of cAMP and cGMP to modulate intracellular effects. PDE4 is mainly expressed in inflammatory cells, and its inhibition leads to reduced inflammatory cell activity. Activation of the cellular immune system and autoimmunity are hallmarks of the pathogenesis of systemic sclerosis (SSc). Objectives: To study the disease-modifying, anti-fibrotic effects of PDE4 inhibition in preclinical models of SSc. Methods: The effects of the PDE4-specific inhibitors rolipram and apremilast were studied in the models of bleomycin-induced skin fibrosis and sclerodermatous chronic graft versus host disease (sclGvHD), reflecting local and systemic inflammatory fibrotic disease. To better understand the disease-modifying activity of PDE4 blockade in preclinical SSc, we investigated fibrosis relevant genes and cytokines in fibroblasts and macrophages from healthy individuals and patients suffering from diffuse-cutaneous SSc upon blockade of PDE4. Results: We first studied PDE4 inhibition by rolipram in a preventive bleomycin model. In this model, rolipram reduced skin thickening by 33% ( p <0.001), the amount of fibrotic tissue assessed by histomorphometry by 38% ( p =0.016) and the number of α-SMA-positive myofibroblasts by 45% ( p <0.001). We then wondered if the clinically approved PDE inhibitor apremilast did also show significant anti-fibrotic activity, and if PDE inhibition did not only prevent but also treat fibrosis once it was established. In a modified bleomycin model of established fibrosis, apremilast reduced skin thickness by 26% (p=0.001) the amount of fibrotic tissue by 21% (p=0.037) and the number of myofibroblasts by 73% (p=0.001). Taking advantage of a model of cGvHD, we investigated if PDE4 blockade could also reduce fibrosis in a model for systemic fibrotic disease. Indeed, rolipram reduced skin thickness by 33% ( p =0.002), the amount of fibrotic tissue by 35% (p=0.016) and of the number of α-SMA-positive myofibroblasts by 46% ( p =0.002). In line with the general mode of action of PDE4 blockade, we observed significantly reduced leukocytic infiltration in the fibrotic skin of all three animal models. We further demonstrated that fibroblasts were not the direct targets of the anti-fibrotic effects of PDE4 blockage. By contrast, PDE4 inhibition decreased the release of pro-fibrotic cytokines interleukin-6 and 13 (IL-6, IL-13) and, transforming growth factor β1 and β2 (TGFβ1, TGFβ2) and fibronectin-1 (FN-1) from activated M2 macrophages obtained from both healthy volunteers and SSc patients, resulting in reduced fibroblast activation and collagen release. Conclusions: PDE4 inhibition reduces inflammatory cell activity and the release of pro-fibrotic cytokines from M2 macrophages, which leads to decreased fibroblast activation and collagen release. Importantly, apremilast is already approved by the FDA and the EMA for the treatment of psoriatic arthritis. Therefore, our preclinical results might prompt the use of PDE4 inhibitors in clinical studies with patients suffering from SSc. Our findings suggest that particularly patients with inflammation-driven fibrosis might benefit from PDE4 blockade. References: Manning CD et al.: Suppression of human inflammatory cell function by subtype-selective PDE4 inhibitors correlates with inhibition of PDE4A and PDE4B. Br J Pharmacol 1999, 128:1393–1398 Disclosure of Interest: None declared